Pengaruh Penerapan Model Pembelajaran Auditory Intellectually Repetition (Air) Terhadap Hasil Belajar Tematik Siswa Kelas VI SD Sabir (Sekolah Alam Bireun) - Muthmainnah, Muthmainnah (Genderang Asa: Journal of Primary Education, 2024)
A less than optimal learning process can result in low learning outcomes. In improving student learning outcomes, it is necessary to apply a learning model that is appropriate to the material presented in the learning process so that the planned learning objectives can be achieved. One alternative learning model that is suitable for thematic learning is the Auditory Intellectually Repetition (AIR) learning model. The Auditory Intellectually Repetition (AIR) learning model emphasizes 3 aspects, namely learning by listening, critical thinking, and repetition. The aim of this research was to determine the effect of implementing the Auditory Intellectually Repetition (AIR) learning model on the thematic learning outcomes of class VI students at SABIR Elementary School. The research approach used is a quantitative approach with experimental research type. The results of the research show that the application of the Auditory Intellectually Repetition (AIR) learning model has a significant effect on the thematic learning outcomes of Class VI students at SABIR Elementary School.